John Galsworthy and Slum Clearance. - Durey, Jill Felicity (Texas Studies in Literature & Language)
The article presents literary criticism of books of John Galsworthy. Topics include the book "The Man of Property" about upper-middle-class families, the book "The Island Pharisees" about an uncaring high society, and the book "Fraternity" about a gradual exodus by the middle classes from inner London, England in the twentieth century.